SPIRAL, FUNCTIONS AND OSCILLATING SYSTEMS BESSEL - Gil Benitez, W. (1998)
lt is shown a mathematics analysis that link spirals, differential equations of second order of the Bessel function type and the oscillant systems with constant and variable frequency. lt is found that the oscillant systems are consecuents to a spiral mathematical functions and Bessel is only some of its varieties. Consequently is shown an exact solution of the Bessel equations which does l'lot require tables. The math model it is a tool which will be used to simulate oscillant phenomena with. Variable frequency that is show up in solid-liquid interface, adsorption, crystallization, condensation and solidífication.